Shariah auditing in Islamic financial institutions: exploring the gap between the "desirable" and the "actual" - Kasim, Nawal; Mohamad Ibrahim, Shahul Hameed; Sulaiman, Maliah (World Business Institute, Australia, 2009)
Persistently high expectations from the operations of Islamic financial institutions (IFIs) appears to give way for a gap to exist between “what ought to be” shariah auditing and the current practice of shariah audit in IFIs in Malaysia. Sulaiman (2005) mentioned that “what ought to be desired (the desirable)” may not coincide with “what is actually desired (the desired)” and in consequent “what is actually desired” may not be the same as “the actual” practice. This paper aims to explore empirically the gap between “the desired” and “the actual” practice of shariah auditing in IFIs in Malaysia. It is found that there exists a gap between the two concepts in terms of certain issues discussed in this study. Even though this paper cannot hope to bridge the gap that exists, it nevertheless shows that shariah audit function has not seriously taken an impact in IFIs in Malaysia despite its potential as a monitoring tool for shariah compliance